Gender preference and its impact on families: a cross sectional study - Dadwani, Roma S.; Koringa, Hetal T.; Kartha, Girija P. (International Journal Of Community Medicine And Public Health, 2019)
Background: Despite tremendous economic progress made through liberalization and globalization, gender preference for children remains a major issue in any society throughout the globe. The aim of the study was to determine the gender preference for children and its impact on family among study population. Methods: A cross sectional study was carried out between October-2013 to December-2013 in the urban (Ratanpar) and rural (Khodu village) field practice area of C U Shah Medical College Surendranagar, Gujarat. Total 377 study participants were selected by using systematic random sampling. Data was collected using pre designed and pre tested questionnaire and analyzed using SPSS. Results: Out of total study population, about 78.8% were completed their family and 21.2% had desire for child in near future. Those who had completed their family, nearly two third of them were blessed with both male and female child (62%). Among those who had desire for child (n=80), about two fifth (41.2%) wished to have male child. At parity one, 52% had desire for only male child as next child and also strong preference for male child was observed at parity two and above among those having only female children. Conclusions: Study revealed that most of the couples wish to have at least one son in the family hence perception of parents towards desired gender of child to be born must be gravitated in favor of daughters.